2010
DOI: 10.1002/14651858.cd001973.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating oral mucositis for patients with cancer receiving treatment

Abstract: BackgroundTreatment of cancer is increasingly effective but associated with short and long term side effects. Oral side effects, including oral mucositis (mouth ulceration), remain a major source of illness despite the use of a variety of agents to treat them. ObjectivesTo assess the effectiveness of interventions for treating oral mucositis or its associated pain in patients with cancer receiving chemotherapy or radiotherapy or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(106 citation statements)
references
References 76 publications
1
101
1
3
Order By: Relevance
“…A possible limitation to our findings is the small sample size of the included trials. Our finding is partly contradicting a Cochrane review [6] which was recently updated [37]. Our review deviates from their conclusions because we have included more studies and subgroup analyses by dose range and wavelengths.…”
Section: Discussioncontrasting
confidence: 97%
“…A possible limitation to our findings is the small sample size of the included trials. Our finding is partly contradicting a Cochrane review [6] which was recently updated [37]. Our review deviates from their conclusions because we have included more studies and subgroup analyses by dose range and wavelengths.…”
Section: Discussioncontrasting
confidence: 97%
“…Many studies have been carried out on mucositis owing to its importance and although there are various drugs to prevent and treat mucositis (Table 1), there is no gold-standard protocol that is prominently better than the rest. Despite all these treatment options 28,64,133,151 the strategies to reduce oral mucositis are still unclear. This is because there is not enough evidence describing a treatment with proven efficiency to surpass the other treatments.…”
Section: Treatmentmentioning
confidence: 99%
“…Clarkson et al [79] and Worthington et al [43] concluded that topical or systemic GM-CSF cannot be recommended for prevention or treatment of oral mucositis. alloHSCT allogeneic hematopoietic stem cell transplantation, autoHSCT autologous hematopoietic stem cell transplantation (C), RT (chemo)radiation therapy, CT chemotherapy, EGF epidermal growth factor, HD high-dose, H&N head and neck, HSCT hematopoietic stem cell transplantation, iv intravenous, FGF fibroblast growth factor, 5-FU 5-fluoroucil, G-CSF granulocyte-colony stimulating growth factor, GM-CSF granulocyte-macrophage colony-stimulating growth factor, IL-11 interleukin-11, KGF keratinocyte growth factor, P prevention, RT radiotherapy, sc subcutaneously, syst systemically, T treatment, TBI total body irradiation, TGF-β transforming growth factor-beta…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%